A long-lasting heat insulation film

A heat-insulating film with tungsten complex infrared absorbers and polyaniline nanomaterials in acrylic resin ensures long-term thermal insulation and color stability by dual reflection and absorption, addressing compatibility and degradation issues in existing films.

CN118876537BActive Publication Date: 2024-12-31CHANGDI NEW MATERIAL TECHNOLOGY (SHANGHAI) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411379362.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-31
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Existing thermal insulation films face issues with optical absorption layers made of organic light-absorbing dyes that degrade under light and heat, leading to reduced thermal insulation effectiveness over time, while inorganic materials have poor compatibility with organic systems and lower light transmittance.

Method used

A heat-insulating film with an optical reflective layer and optical absorption layers on both sides, composed of tungsten complex infrared absorbers and polyaniline nanomaterials, which are compatible with acrylic resin and provide dual reflection and absorption for near-infrared and ultraviolet light, maintaining high solar energy blocking rates and color stability.

Benefits of technology

The film achieves long-term high-efficiency heat insulation and stable color rendering with minimal change in total solar energy blocking rate, despite prolonged sunlight exposure, through the combination of optical reflective and absorption layers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118876537B_ABST
    Figure CN118876537B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of optical films, and specifically discloses a long-lasting heat-insulating film. The heat-insulating film comprises an optical reflective layer and an optical absorption layer arranged on both sides of the optical reflective layer. The optical absorption layer is composed of a tungsten complex infrared absorber, a polyaniline nanomaterial, a dispersant, an initiator and an acrylic resin; wherein the tungsten complex infrared absorber is obtained by reacting tungsten hexachloride with a neutral phosphate solvent; the optical reflective layer is obtained by alternately laminating at least two thermoplastic resins, and the first reflection peak generated by the optical reflective layer is located in the 680-1440nm band, and the second reflection peak generated is located in the 220-480nm band. The heat-insulating film achieves efficient heat insulation through the dual effects of reflection and absorption, and the total solar energy blocking rate exceeds 55%. After long-term use, the total solar energy blocking rate changes very little, and the long-term heat insulation stability is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of optical films, and more particularly to a long-lasting heat-insulating film. Background Art

[0002] With the development of science and technology, thermal insulation films in the fields of construction, automobiles, etc. have become an important choice for people to pursue a comfortable life. Thermal insulation films have undergone many technical improvements such as dyed films, metal films, and multi-layer micro-laminated films. Multi-layer micro-laminated films include laminated thermal insulation functional layers, and protective layers and optical absorption layers are arranged on both sides of the laminated thermal insulation functional layers in sequence. Through the combined action of the laminated thermal insulation functional layers and the optical absorption layers, efficient thermal insulation is achieved.

[0003] At present, the optical absorption layer is generally formed on the protective layer by mixing optical absorbers with glue through coating and other means. Optical absorbers are generally divided into inorganic materials and organic light-absorbing dyes. Inorganic materials include carbon-based nanomaterials such as copper sulfide, carbon nanotubes and graphene. Inorganic materials have a wide absorption wavelength range and good light and heat stability, but poor compatibility with organic systems, and the light transmittance of the optical absorption layer decreases, which limits its development in thermal insulation films. Organic light-absorbing dyes have poor tolerance to light and heat, and are easily decomposed and ineffective, making it difficult for the optical absorption layer to maintain a long-term thermal insulation effect.

[0004] After actual testing, it was found that the optical absorption layer made of organic light-absorbing dyes and the laminated thermal insulation functional layer showed different degrees of fading and a decrease in the total solar energy blocking rate after 24 months of use. Summary of the invention

[0005] The present application provides a long-lasting thermal insulation film, so that the thermal insulation film can have both excellent and stable thermal insulation effect and good color rendering effect when used for a long time.

[0006] The present application provides a long-lasting thermal insulation film, which adopts the following technical solution:

[0007] A heat-insulating film with dimming function, comprising an optical reflective layer and optical absorption layers arranged on both sides of the optical reflective layer;

[0008] The optical absorption layer is composed of the following components in parts by weight: 0.01 to 0.06 parts of tungsten complex infrared absorber, 0.42 to 1.35 parts of polyaniline nanomaterial, 1.6 to 3.2 parts of dispersant, 0.12 to 0.39 parts of initiator and 95 to 97.85 parts of acrylic resin;

[0009] Wherein, the tungsten complex infrared absorber is obtained by reacting tungsten hexachloride with a neutral phosphate solvent;

[0010] The optical reflective layer is obtained by alternately laminating at least two thermoplastic resins. The first reflective peak generated by the optical reflective layer is located in the 680-1440nm band, and the second reflective peak generated by the optical reflective layer is located in the 220-480nm band.

[0011] By adopting the above technical solution, the present application adopts the combination of an optical reflective layer and an optical absorption layer to achieve the effects of long-term high-efficiency heat insulation and stable color rendering. The principle is as follows:

[0012] The optical absorption layer uses tungsten complex infrared absorber and polyaniline nanomaterial as near-infrared band absorbers; tungsten complex infrared absorber is an organic metal chelate with hexavalent tungsten ion as the center and phosphate as the ligand. The tungsten ion is modified by phosphate and has good compatibility in acrylic resin; polyaniline nanomaterial is polymerized by aniline, and the phosphate segment of tungsten complex infrared absorber contains phosphate group, which can form hydrogen bond with nitrogen atom in polyaniline, so as to promote the compatibility of polyaniline nanomaterial in acrylic resin; according to the spectral transmittance curve of the optical absorption layer, it can be known that the optical absorption layer has strong absorption for the near-infrared band of 700-1400nm, and has excellent absorption performance for the near-infrared band, and has high transmittance in the visible light band of 480-680nm; the optical reflection layer reflects the near-infrared band of 680-1440nm, and realizes efficient heat insulation through the dual effects of reflection and absorption, and the total solar energy blocking rate exceeds 55%;

[0013] The second reflection peak of the optical reflection layer is located in the 220-480nm band. The optical reflection layer can reflect ultraviolet light, and the polyaniline nanomaterial of the optical absorption layer absorbs the ultraviolet band, so that the ultraviolet radiation has little effect on the thermal insulation film. Under long-term solar radiation, the total solar energy blocking rate of the thermal insulation film changes very little; the thermal insulation film has excellent stability as a whole;

[0014] Interference and diffraction will cause light of specific wavelengths to interfere with each other, forming a special optical effect. The optical reflective layer presents different visual effects at different viewing angles. When light is incident from the front at a certain angle, the interference and diffraction effects are relatively weak, and there is a certain reflectivity in the 220nm~480nm band. At the front viewing angle, the optical reflective layer appears light blue. The optical absorption layer has a high transmittance in the visible light band. The optical reflective layer and the optical absorption layer are composited, and the coloring effect of the thermal insulation film depends on the optical reflective layer. Since the optical absorption layer is located on both sides of the optical reflective layer, it protects the optical reflective layer. Under long-term sunlight irradiation, the first reflection peak and the second reflection peak of the optical reflective layer do not change, and the coloring effect of the thermal insulation film is stable.

[0015] Furthermore, the weight ratio of the tungsten complex infrared absorber to the polyaniline nanomaterial in the optical absorption layer is 1:(30-40).

[0016] By adopting the above technical scheme and adjusting the weight ratio between the tungsten complex infrared absorber and the polyaniline nanomaterial, the polyaniline nanomaterial can be better dispersed in the acrylic resin, with less influence on the visible light transmittance, thereby improving the visible light transmittance of the optical absorption layer; and the transmittance in the near-infrared band can be reduced, thereby ensuring that the total solar energy blocking rate of the thermal insulation film is maintained at a high level.

[0017] Furthermore, the size of the polyaniline nanomaterial is 120-180 nm.

[0018] Furthermore, the dispersant is one or more of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, and polyethylene glycol.

[0019] Furthermore, the dispersant is polyethylene glycol.

[0020] By adopting the above technical scheme, the dispersant promotes the uniform dispersion of the polyaniline nanomaterial in the acrylic resin; at the same time, the polyethylene glycol contains a long alkyl chain segment, and the tungsten complex infrared absorber contains a flexible phosphate chain segment. The two interact with each other to make up for the defect of the high molecular weight polyaniline chain segment causing the rigidity enhancement of the optical absorption layer, thereby helping to dissipate the large stress gradient at the interface between the melt and the flow channel wall of the optical reflective layer, and protecting the structure of the optical reflective layer from being destroyed.

[0021] Furthermore, the physical thickness ratio of the optical absorption layer to the optical reflection layer on one side is 1:(20-25).

[0022] Furthermore, the physical thickness ratio of the optical absorption layer to the optical reflection layer on one side is 1:22.5.

[0023] By adopting the above technical solution, the thickness ratio between the optical absorption layer and the optical emission layer is controlled within a moderate range, taking into account the balance between the total solar energy blocking rate and the visible light transmittance of the thermal insulation film.

[0024] Furthermore, the optical absorption layer and the optical reflection layer are formed by a one-step casting method.

[0025] By adopting the above technical solution, the acrylic resin of the optical absorption layer is re-granulated and formed synchronously with the optical reflection layer; this method can not only make the tungsten complex infrared absorber and the polyaniline nanomaterial evenly distributed in the acrylic resin, but also reduce the molding steps of the thermal insulation film and simplify the production process.

[0026] In the present application, the two thermoplastic resins of the optical reflective layer are respectively recorded as thermoplastic resin A and thermoplastic resin B, and the refractive index difference between thermoplastic resin A and thermoplastic resin B is ≥ 0.05, which can be expressed by the following formula: m =2 / m×(n A d A +n B d B ); m It represents the central wavelength of the mth reflection peak, m represents the order or level of the reflection peak, n A is the refractive index of thermoplastic resin A, n B is the refractive index of thermoplastic resin B, d A ,d B is the thickness of the adjacent A layer and B layer. According to the above formula, the center position of each level of reflection peak after lamination can be calculated, so as to adjust the band range of the reflection peak.

[0027] Wherein, the thermoplastic resin A and the thermoplastic resin B are at least one selected from polyolefin resins, polyamide resins, copolymer resins of vinyl monomers, acrylic resins, polyester resins, polyether resins, cellulose ester resins, and biodegradable polymers:

[0028] Among them, polyolefin resins include, but are not limited to, polyethylene, polypropylene, poly(1-butene), poly(4-methylpentene), polyisobutylene, polyisoprene, polybutadiene, polyvinylcyclohexane, polystyrene, poly(α-methylstyrene), poly(p-methylstyrene), polynorbornene, and polycyclopentene;

[0029] Polyamide resins, including but not limited to nylon 6, nylon 11, nylon 12, and nylon 66;

[0030] Copolymer resins of vinyl monomers, including but not limited to ethylene / propylene copolymers, ethylene / vinyl cyclohexane copolymers, ethylene / vinyl cyclohexene copolymers, ethylene / alkyl acrylate copolymers, ethylene / alkyl methacrylate copolymers, ethylene / norbornene copolymers, ethylene / vinyl acetate copolymers, propylene / butadiene copolymers, isobutylene / isoprene copolymers, vinyl chloride / vinyl acetate copolymers;

[0031] Acrylic resins, including but not limited to polyacrylate, polymethacrylate, polymethyl methacrylate, polyacrylamide, polyacrylonitrile, etc.;

[0032] Polyester resins, including polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, and polyethylene 2,6-naphthalate;

[0033] Polyether resins, including but not limited to polyethylene oxide, polypropylene oxide, polyalkylene glycol, etc.;

[0034] Cellulose ester resins, including but not limited to diacetyl cellulose, triacetyl cellulose, propionyl cellulose, butyryl cellulose, acetyl propionyl cellulose, and nitrocellulose;

[0035] Biodegradable polymers, including but not limited to polylactic acid, polybutylene succinate, etc.; as well as polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, polyvinyl butyral, polyacetal, polyglycolic acid, polycarbonate, polyketone, polyether sulfone, polyether ether ketone, modified polyphenylene ether, polyphenylene sulfide, polyetherimide, polyimide, polysiloxane, tetrafluoroethylene, trifluoroethylene resin, trifluorochloroethylene resin, tetrafluoroethylene-hexafluoropropylene copolymer, polyvinylidene fluoride. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is the spectral transmittance curve of the optical absorption layer of the thermal insulation film made in Example 1.

[0037] Figure 2 This is the reflection spectrum of the optical reflection layer of the thermal insulation film prepared in Example 1.

[0038] Figure 3 This is the reflection spectrum of the optical reflection layer of the thermal insulation film prepared in Example 7.

[0039] Figure 4 This is the reflection spectrum of the optical reflection layer of the thermal insulation film prepared in Example 8. DETAILED DESCRIPTION

[0040] Unless otherwise specified, the sources of raw materials for each preparation example, embodiment and comparative example of this application are as follows:

[0041] Tungsten hexachloride: analytical grade;

[0042] Tributyl phosphate: analytical grade;

[0043] Polyacrylate: Brand EA-1010;

[0044] Sodium dodecyl sulfate: analytical grade;

[0045] Polyethylene glycol: brand PEG-200;

[0046] Azobisisobutyronitrile: analytical grade;

[0047] PET: Brand FG612, from Yizheng Chemical Fiber;

[0048] PMMA: brand HBS006H, from Mitsubishi;

[0049] PETG: Brand S2008, from SK, South Korea.

[0050] Preparation Example A

[0051] Tungsten complex infrared absorber is prepared according to the following steps:

[0052] Weigh 1kg of tungsten hexachloride and 5kg of tributyl phosphate, heat the tributyl phosphate in a water bath, add tungsten hexachloride under stirring until the tungsten hexachloride is completely dissolved in the tributyl phosphate, filter and purify to obtain a liquid tungsten complex infrared absorber.

[0053] Preparation Example B

[0054] Polyaniline nanomaterials are prepared according to the following steps:

[0055] Weigh 1 kg of sodium dodecylbenzene sulfonate and 1.23 kg of ammonium persulfate, dissolve the sodium dodecylbenzene sulfonate and aniline in a hydrochloric acid chloroform solution (HCl:CCl4=100:0.8, v / v), mix well, and use as the aqueous phase for later use;

[0056] Take 0.51 kg of aniline and dissolve it in 5 L of chloroform as the oil phase;

[0057] The oil phase was continuously added to the water phase at a rate of 1 mL / s, the temperature of the addition was controlled to be 10°C, and the reaction was kept warm for 12 hours. After the reaction was completed, the polyaniline nanomaterial was obtained by centrifugation; after washing with chloroform three times, the polyaniline nanomaterial was dried at 60°C, and the chloroform was recovered to obtain the polyaniline nanomaterial;

[0058] The polyaniline nanomaterials with an average particle size of less than 100 nm, an average particle size of 120 to 180 nm, and an average particle size of more than 200 nm are screened out respectively.

[0059] Example

[0060] Example 1

[0061] A long-lasting heat-insulating film is prepared according to the following steps:

[0062] S1. Granulation of optical absorption layer:

[0063] Weigh 0.04 g of tungsten complex infrared absorber (from Preparation Example A), 1.2 g of polyaniline nanomaterial (from Preparation Example B, with an average particle size of 120 to 180 nm), 2.5 g of dispersant PEG-200, 0.26 g of initiator azobisisobutyronitrile and 96 g of acrylic resin EA-1010, mix the above substances evenly, and granulate them through an extruder to obtain a near-infrared light-absorbing resin;

[0064] S2, one-step casting of optical reflection layer and optical absorption layer:

[0065] PET resin with a refractive index of 1.65 after double drawing and PMMA resin with a refractive index of 1.49 were selected, and a dispenser was used to design the film structure of the optical reflective layer. PET and PMMA were alternately laminated in the dispenser with different gradient thicknesses.

[0066] The designed primary reflection band is 700-860nm, while the secondary reflection peak appears at 350-430nm, and the total number of optical layers is 250;

[0067] The optical thickness of the initial PET layer is 178.0 nm. The stacking design adopts a linear increasing method. According to a certain linear increase rule, then:

[0068] Since λ1=2 / 1×(n A d A +n B d B ), the optical thickness of the initial PMMA layer can be calculated to be 172.0 nm;

[0069] The PET layer gradually increases from an initial optical thickness of 178.0 nm to a final optical thickness of 218.0 nm; the corresponding PET layer gradually increases from an initial physical thickness of 108 nm to a final physical thickness of 132 nm;

[0070] Similarly, the PMMA layer gradually increases from an initial optical thickness of 172 nm to a final optical thickness of 212 nm; the corresponding physical thickness of the PMMA layer gradually increases from 115.4 nm to a final physical thickness of 142 nm;

[0071] Cumulative superposition can be used to calculate the total physical thickness of the optical reflective layer to be 31 μm;

[0072] Near-infrared light-absorbing resin is put into the dispenser to form optical absorption layers on both sides of the optical reflection layer. The physical thickness of the single-sided optical absorption layer is 1.4 μm, forming a long-lasting heat-insulating film.

[0073] Example 2

[0074] A long-lasting heat-insulating film, which is different from Example 1 in that the resin composition of the optical absorption layer is different, as follows:

[0075] Weigh 0.03 g of tungsten complex infrared absorber (from Preparation Example A), 1.2 g of polyaniline nanomaterial (from Preparation Example B, with an average particle size of 120 to 180 nm), 2.5 g of dispersant PEG-200, 0.27 g of initiator azobisisobutyronitrile and 96 g of acrylic resin EA-1010, mix the above substances evenly, and granulate them through an extruder to obtain a near-infrared absorbing resin.

[0076] Example 3

[0077] A long-lasting heat-insulating film, which is different from Example 1 in that the resin composition of the optical absorption layer is different, as follows:

[0078] Weigh 0.01 g of tungsten complex infrared absorber (from Preparation Example A), 0.42 g of polyaniline nanomaterial (from Preparation Example B, with an average particle size of 120 to 180 nm), 1.6 g of dispersant PEG-200, 0.12 g of initiator azobisisobutyronitrile and 97.85 g of acrylic resin EA-1010, mix the above substances evenly, and granulate them through an extruder to obtain a near-infrared absorbing resin.

[0079] Example 4

[0080] A long-lasting heat-insulating film, which is different from Example 1 in that the resin composition of the optical absorption layer is different, as follows:

[0081] Weigh 0.06 g of tungsten complex infrared absorber (from Preparation Example A), 1.35 g of polyaniline nanomaterial (from Preparation Example B, with an average particle size of 120-180 nm), 3.2 g of dispersant sodium dodecyl sulfate, 0.39 g of initiator azobisisobutyronitrile and 95 g of acrylic resin EA-1010, mix the above substances evenly, and granulate them through an extruder to obtain a near-infrared absorbing resin.

[0082] Example 5

[0083] A long-lasting heat-insulating film is different from Example 1 in that the average particle size of the polyaniline nanomaterial is different. In this example, polyaniline nanomaterials with an average particle size of less than 100 nm are selected by weight to replace polyaniline nanomaterials with an average particle size of 120 to 180 nm.

[0084] Example 6

[0085] A long-lasting heat-insulating film is different from Example 1 in that the average particle size of the polyaniline nanomaterial is different. In this example, polyaniline nanomaterials with an average particle size of >200 nm are selected to replace polyaniline nanomaterials with an average particle size of 120-180 nm by weight.

[0086] Example 7

[0087] A long-lasting heat-insulating film, which is different from Example 1 in that the structures of the optical reflective layer and the optical absorption layer are different, as follows:

[0088] PET resin with a refractive index of 1.65 after double drawing and PETG resin with a refractive index of 1.57 were selected, and a dispenser was used to design the film structure of the optical layer. PET and PETG were alternately laminated in the dispenser with different gradient thicknesses.

[0089] The primary reflection band is designed to be 1230-1320nm, where the optical thickness of the PET layer and PETG is equal, thereby suppressing the secondary reflection peak and generating the tertiary reflection peak, which appears in the band of 410-440nm; the thickness of the optical layer is 220 layers;

[0090] Since λ1=2 / 1×(n A d A +n B d B ), and n A d A =n B d B , from which it can be calculated that the optical thickness of the initial PET layer and the initial PETG layer are both 307.5nm, and the physical thickness of the initial PET layer can be calculated to be 186.36nm, and the physical thickness of the initial PETG layer can be calculated to be 195.86nm;

[0091] The stacking thickness design of the PET layer and the PETG layer adopts a linear gradual increase method. According to a certain linear increase rule, similarly, it can be calculated that the optical thickness of the last PET layer and the last PETG layer are both 330nm; correspondingly, the physical thickness of the last PET layer can be calculated to be 200nm, and the physical thickness of the last PETG layer can be calculated to be 210.19nm;

[0092] Cumulative superposition can be used to calculate that the total physical thickness of the dimming and heat insulation functional layer is 44 μm;

[0093] Near-infrared light-absorbing resin is put into the dispenser to form optical absorption layers on both sides of the optical reflection layer. The physical thickness of the single-sided optical absorption layer is 2.2 μm, forming a long-lasting heat-insulating film.

[0094] Example 8

[0095] A long-lasting heat-insulating film, which is different from Example 1 in that the structures of the optical reflective layer and the optical absorption layer are different, as follows:

[0096] PET resin with a refractive index of 1.65 after double drawing and PMMA resin with a refractive index of 1.49 were selected, and a dispenser was used to design the film structure of the optical layer. PET and PMMA were alternately laminated in the dispenser with different gradient thicknesses.

[0097] The primary reflection band is designed to be 1230-1410nm, where the optical thickness of the PET layer and the PMMA layer is equal, thereby suppressing the secondary reflection peak and generating a tertiary reflection peak, which appears in the band of 410-470nm; the thickness of the optical layer is 320 layers;

[0098] Since λ1=2 / 1×(n A dA +n B d B ), and n A d A =n B d B , from which it can be calculated that the optical thickness of the initial PET layer and the initial PMMA layer are both 307.5nm, and the physical thickness of the initial PET layer can be calculated to be 186.36nm, and the physical thickness of the initial PMMA layer can be calculated to be 206.37nm;

[0099] The stacking thickness design of the PET layer and the PMMA layer adopts a linear gradual increase method. According to a certain linear increase rule, the optical thickness of the last PET layer and the last PMMA layer can be calculated to be 352.5nm; the physical thickness of the last PET layer can be calculated to be 213.64nm, and the physical thickness of the last PMMA layer can be calculated to be 236.58nm.

[0100] Cumulative superposition can be used to calculate that the total physical thickness of the dimming and heat insulation functional layer is 67 μm;

[0101] Near-infrared light-absorbing resin is put into the dispenser to form optical absorption layers on both sides of the optical reflection layer. The physical thickness of the single-sided optical absorption layer is 2.7 μm, forming a long-lasting thermal insulation film.

[0102] Comparative Example

[0103] Comparative Example 1

[0104] A heat insulation film is different from the embodiment 1 in that the composition of the resin used in the optical absorption layer is different, specifically, an equal weight portion of a tungsten complex infrared absorber is used to replace the polyaniline nanomaterial.

[0105] Comparative Example 2

[0106] A heat insulation film is different from the embodiment 1 in that the composition of the resin used in the optical absorption layer is different, specifically, polyaniline nanomaterials are used in equal parts by weight to replace the tungsten complex infrared absorber.

[0107] Comparative Example 3

[0108] A thermal insulation film, which is different from Example 1 in that: in this comparative example, PET resin is extruded on both sides of the optical reflective layer as a protective layer, and nano ATO transparent thermal insulation coating is further coated on the protective layer, which is cured to form an optical barrier layer (commercially available, sourced from Guangdong Paile Intelligent), and the physical thickness of the protective layer and the optical barrier layer are controlled to be 2 μm.

[0109] Test results

[0110] Table 1. Test results of Examples 1-8 and Comparative Examples 1-3

[0111]

[0112] Note: The test conditions of the salt spray test are: within the temperature range of -10℃~50℃, at a speed of 1℃ / min, for 240h, and the relative humidity is 100%;

[0113] According to Table 1 and Figure 1-4 It can be seen that the optical absorption layer has a lower transmittance in the ultraviolet light band and the infrared light band, that is, the optical absorption layer can absorb ultraviolet light and infrared light well; the optical reflection layer has a higher reflectivity in the ultraviolet light band and a certain infrared light band; and the optical absorption layer has a higher transmittance in the visible light band, and the optical reflection layer has a lower reflectivity in the visible light band. Therefore, the thermal insulation film has good transmittance in the visible light band and excellent visibility.

[0114] Example 1 forms a single comparison with Comparative Example 1 and Comparative Example 2. In Comparative Example 1, only tungsten complex near-infrared absorber is used in the optical absorption layer, and in Comparative Example 2, only polyaniline nanomaterial is used in the optical absorption layer. The total solar energy blocking rate of Comparative Example 1 and Comparative Example 2 is lower than that of Example 1. The reason is that the bands with low transmittance of tungsten complex infrared absorber and polyaniline nanomaterial are not the same bands. Therefore, the compound use of tungsten complex infrared absorber and polyaniline nanomaterial can expand the range of infrared band and ultraviolet band with low transmittance, thereby improving the total solar energy blocking rate. At the same time, the content of tungsten complex near-infrared absorber in Comparative Example 1 is increased. The tungsten complex near-infrared absorber itself is blue and has a high reflectivity to blue light. After increasing the content of tungsten complex near-infrared absorber, the front view of the thermal insulation film shows a clear blue color. Similarly, the polyaniline nanomaterial itself is green. The use of a large amount of polyaniline nanomaterial makes the front view of the thermal insulation film show a clear green color. In Example 1, since the total content of the polyaniline nanomaterial and the tungsten complex near-infrared absorber is relatively low, the color at the front viewing angle is light while ensuring that the thermal insulation film has a good total solar energy blocking rate.

[0115] Example 1 is compared with Comparative Example 3. In Comparative Example 3, a commercially available optical absorber is used and coated on the outside of the PET protective layer in steps. The optical absorber has poor weather resistance and is easily oxidized, fails, and falls off, resulting in a significant reduction in the total solar energy blocking rate of the thermal insulation film.

[0116] In contrast to Examples 1-4, the difference lies in the different total contents of the tungsten complex infrared absorber and the polyaniline nanomaterial in the optical absorption layer. Although the increase in the total content of the tungsten complex infrared absorber and the polyaniline nanomaterial helps to improve the total solar energy blocking rate of the thermal insulation film, it will cause a significant decrease in the visible light transmittance. Therefore, it is necessary to strictly control the total content of the tungsten complex infrared absorber and the polyaniline nanomaterial.

[0117] In contrast to Examples 1, 7-8, the difference lies in that the reflectivity and reflection band range of the optical reflective layer are different. According to the reflection spectrum and detection data, the lamination method of the optical reflective layer will affect the reflectivity and transmittance. The lamination method of Example 7 enables the thermal insulation film to have better reflection effects in the near-infrared band and the ultraviolet band, and weak reflection effect on the visible light band, so that the total solar energy blocking rate and visible light transmittance of the thermal insulation film are improved simultaneously.

[0118] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0119] Moreover, the above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. A long-lasting thermal insulation film, characterized in that: It comprises an optical reflective layer and an optical absorption layer arranged on both sides of the optical reflective layer; The optical absorption layer is composed of the following components in parts by weight: 0.01 to 0.06 parts of tungsten complex infrared absorber, 0.42 to 1.35 parts of polyaniline nanomaterial, 1.6 to 3.2 parts of dispersant, 0.12 to 0.39 parts of initiator and 95 to 97.85 parts of acrylic resin; Wherein, the tungsten complex infrared absorber is obtained by reacting tungsten hexachloride with a neutral phosphate solvent; The optical reflective layer is obtained by alternately laminating at least two thermoplastic resins. The first reflective peak generated by the optical reflective layer is located in the 680-1440nm band, and the second reflective peak generated by the optical reflective layer is located in the 220-480nm band.

2. A long-lasting thermal insulation film according to claim 1, characterized in that: The weight ratio of the tungsten complex infrared absorber to the polyaniline nanomaterial in the optical absorption layer is 1:(30-40).

3. The long-lasting thermal insulation film according to claim 1, characterized in that: The size of the polyaniline nanomaterial is 120-180 nm.

4. The long-lasting thermal insulation film according to claim 1, characterized in that: The dispersant is one or more of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide and polyethylene glycol.

5. A long-lasting thermal insulation film as claimed in claim 4, characterized in that: The dispersant is polyethylene glycol.

6. A long-lasting thermal insulation film as claimed in claim 1, characterized in that: The physical thickness ratio of the optical absorption layer to the optical reflection layer on one side is 1:(20-25).

7. A long-lasting thermal insulation film as claimed in claim 6, characterized in that: The physical thickness ratio of the optical absorption layer to the optical reflection layer on one side is 1:22.

5.

8. The long-lasting thermal insulation film according to claim 7, characterized in that: The optical absorption layer and the optical reflection layer are formed by a one-step casting method.

Citation Information

Patent Citations

  • Heat insulation film and heat insulation material

    CN105984190A

  • Heat-insulating film for window, heat-insulating material for window, and window

    CN106457747A

  • Thermoelectric double-response type color-changing intelligent optical assembly, preparation method and application thereof

    CN111812906A

  • Near-infrared ray absorbent resin composition and method for production thereof

    EP0356027A1

  • Construct with heat-shielding dimming function and glass laminate with light-shielding dimming function

    JP2009244366A